IMPROVING STUDENT LEARNING OUTCOMES IN CLASS 4 ETHNIC DIVERSITY MATERIALS WITH MUTLIPERSPECTIVE - Sofydianty, Angelica (Universitas Lambung Mangkurat, 2023)
Online learning, an event that feels foreign to many stakeholders, but with technological developments it will slowly sync with the changing times. Educational technology is able to replace the stereotypical way of learning into a new one. learning activities using the lecture method and updated using interactive learning (for example using media), using innovative learning emphasizing on process skills, student centered and active earning. as a result deliver positive innovations for student learning. Although the design of information technology-based media must have exclusive skills, it is not that the media should be avoided or abandoned, studying it can be done with various literatures such as books and the internet. Learning media using news technology can be internet, cellphone, flash disk, power point, internet classroom, e-mail, YouTube, and there are still many media that can be used. use includes components of Learning content (LC) and Learning Management System (LMS). so that with the advancement of dynamic technological developments, it is hoped that it will have an impact on the Indonesian generation who will become progressive, transformative, and not beleaguered in the frozen mindset of life. In learning Indonesian diversity in class IV, it is hoped that students will be able to explore the diversity of their own nation and increase their love for the homeland. and not beleaguered in the frozen mindset of life. In learning Indonesian diversity in class IV, it is hoped that students will be able to explore the diversity of their own nation and increase their love for the homeland. and not beleaguered in the frozen mindset of life. In learning Indonesian diversity in class IV, it is hoped that students will be able to explore the diversity of their own nation and increase their love for the homeland.